A General Method to Ultrathin Bimetal‐MOF Nanosheets Arrays via In Situ Transformation of Layered Double Hydroxides Arrays. Issue 6 (15th January 2019) - Wang, Bingqing; Shang, Jing; Guo, Chong; Zhang, Jianze; Zhu, Fengnian; Han, Aijuan; Liu, Junfeng
Abstract: Structure engineering of ultrathin metal–organic framework (MOF) nanosheets to self‐supporting and well‐aligned MOF superstructures is highly desired for diverse applications, especially important for electrocatalysis. In this work, a facile layered double hydroxides in situ transformation strategy is developed to synthesize ultrathin bimetal‐MOF nanosheets (BMNSs) arrays on conductive substrates. This approach is versatile, and applicable to obtain various BMNSs or even trimetal‐MOF nanosheets arrays on different substrates. As a proof of concept application, the obtained ultrathin NiCo‐BDC BMNSs array exhibits an excellent catalytic activity toward the oxygen evolution reaction with an overpotential of only 230 mV to reach a current density of 10 mA cm −2 in 1m KOH. The present work demonstrates a strategy to prepare ultrathin bimetal‐MOF nanosheets arrays, which might open an avenue for various promising applications of MOF materials. Abstract : A general method to fabricate ultrathin bimetal‐MOF nanosheets (BMNSs) arrays via in situ transformation of layered double hydroxide arrays is proposed. A series of BMNSs arrays are successfully fabricated and the obtained BMNSs arrays show excellent performance in catalytic water oxidation. The present strategy might open an avenue to prepare BMNSs arrays with new functionalities for various promising applications.